Pengaruh Perhatian Orang Tua dan Persepsi Siswa Atas Kompetensi Guru Terhadap Prestasi Belajar Ilmu Pengetahuan Sosial - Haris Sulistyo (Herodotus: Jurnal Pendidikan IPS, 2018)
This research is a survey and aims to find and analyze empirically the influence of parents 'attention on the learning achievement of Social Sciences, students' perceptions of teacher competence on learning achievement of Social Sciences, the influence of parental attention and students 'perceptions of teachers' competence collectively against Social Science learning achievement. The research method used is survey. Affordable population in this study are the students of class VII in 3 private junior high schools in Tangerang with 86 samples. The sample of the research is obtained through simple random sampling method that the researchers mix the subjects in the population so that all subjects are considered equal. Collecting data using instrument: questionnaire, and collecting student IPS report cards. The results showed that: 1) There was a significant influence of parents' attention (X1) and students' perceptions of teachers' competence (X2) on learning achievement of Social Sciences (Y), as evidenced by the sig.0,000 <0,05 and Fcitung = 15,000. 2) There is a significant influence of parental attention (X1) on the learning achievement of Social Sciences (Y), this is evidenced by the value of sig.0,000 <0.05 and tcount = 2.861. 3) There is a significant influence of students' perceptions on teacher competence (X2) on learning achievement of Social Sciences (Y), this is proved by sig.0,000 <0,05 and tcount = 3,724. The resulting regression equation is = Y = 21,559 + 0,316 X1 + 0,405 X2